On g-fuzzy cone metric spaces - AYŞEGÜL ÇAKSU GÜLER (Journal of Hyperstructures)
The aim of this paper is to introduce and study the concept of generalized fuzzy cone metric space and to obtain thetopology by using G-fuzzy cone metric. Moreover, the existence of common fixed point theorem for contractive map and occasionally weakly compatible map and is investigated in generalized fuzzy cone metric space.